De Facto exchange rate regime in Korea - Moon, Han Geun (KDI School, 2001)
After the Asian economic crisis in the late 1990s, many East Asian countries including Korea has changed their exchange rate regime from the de facto dollar peg or the managed floating to the free-floating exchange rate regime. However, the common view on the actual exchange rate regime in East Asian countries is that the official labels are different from the actual. Calvo and Reinhart (2000a) expressed this as the “fear of floating”, and Mckinnon (2000) as “after the crisis, the East Asian dollar standard resurrected.” The purpose of this paper is to test the common view on the actual exchange rate regime, using very simple but intuitive OLS regression models based on Frankel and Wei’s work (1994). My regression results show that, firstly, East Asian countries including Korea have returned to the dollar peg or managed floating after the restoration from the crisis, as they did during the pre-crisis period. Possible interpretations are the preponderance of dollar invoicing, the fear of floating, suffering from nominal anchor fragility, not yet overcoming the original sin and the honeymoon effect. The results also show that Korea has substantially changed her exchange rate regime since January 2001, but other countries, even Taiwan and Singapore which had no crisis, are still the same as before. The sensitivity to the dollar has statistically significantly decreased, but sensitivity to the yen is almost twice as much as those in other countries. This result might come from the synchronization of Korean won with Japanese yen from November 2000, changing the monetary policy framework from monetary targeting to the pure inflation targeting, and the full capital and foreign exchange liberalization since the second stage of foreign exchange liberalization (January 2001). However, 6 months (January 2001-June 15, 2001) is not enough to assess policy changes, and, we continuously need to monitor how the exchange rate policy evolves.
Thesis(Master) --KDI School:Master of Business Administration,2001